A unique coincidence of a 17q12 deletion and duplication in a Czech family led to a refined genotype-phenotype correlation - Zunova, Hana; Stolfa, Miroslav; Kunikova, Tereza; Novotna, Drahuse; Valkovicova, Radka; Štěrbová, Katalin; Vlckova, Marketa (American journal of medical genetics. Part A, 2023)
Chromosomal band 17q12 is a gene-rich region flanked by segmental duplications, making the region prone to deletions and duplications via the non-allelic homologous recombination mechanism. While deletions cause a well-described disorder with a specific phenotype called renal cysts and diabetes mellitus, the phenotype caused by reciprocal duplications is less specific, primarily because of variable expressivity, and incomplete penetrance. We present an unusual family with four children carrying the 17q12 microduplication inherited from their clinically healthy mother, who was a carrier of both the duplication and, interestingly, also of an atypical deletion of the 17q12 region. The duplication was inherited from her diabetic father and the deletion from her diabetic mother who also suffered from a renal disorder. Clinical manifestations in the family were variable, but all children showed some degree of a neurodevelopmental disorder, such as epilepsy, intellectual disability, delayed speech development, or attention deficit disorder. The simultaneous occurrence of a deletion and duplication in the same chromosomal region in one family is very rare, and to our knowledge, individuals carrying both a deletion and a duplication of this region have never been described.
Keywords: chromozomální delece; Intellectual Disability; Abnormalities, Multiple; Česká republika; Chromosome Duplication; lidé; Female; fenotyp; Phenotype; duplikace chromozomů; Chromosome Deletion; mnohočetné abnormality; mentální retardace; Czech Republic; ženské pohlaví; Humans